2013
DOI: 10.1371/journal.pone.0069222
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Territories (Lymphosomes) in a Canine: An Animal Model for Investigation of Postoperative Lymphatic Alterations

Abstract: BackgroundLymph node dissection is often performed as a part of surgical treatment for breast cancer and malignant melanoma to prevent malignant cells from traveling via the lymphatic system. Currently little is known about postoperative lymphatic drainage pattern alterations. This knowledge may be useful for management of recurrent cancer and prevention of breast cancer related lymphedema. We mapped the complete superficial lymphatic system of a dog and used this canine model to perform preliminary studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 29 publications
3
83
0
1
Order By: Relevance
“…In addition, in an interesting recent article, Ogata and colleagues used a mouse model of lymphatic injury to show that macrophages play a key role in the early regulation of lymphangiogenesis and that this process may be regulated by interactions with Th1 and Th17 cells (33). Our findings are also supported by lymphangiographic studies in a canine model of axillary lymphadenectomy demonstrating resolution of edema concurrent with development of hyperplastic collateral lymphatics that bypassed the zone of lymphatic injury (34). In the current study, in contrast to that by Ogata and colleagues, we found that macrophage depletion tended to accelerate development of progressive lymphedema, suggesting that the degree of lymphatic stasis is a major regulator of chronic inflammation and pathology.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, in an interesting recent article, Ogata and colleagues used a mouse model of lymphatic injury to show that macrophages play a key role in the early regulation of lymphangiogenesis and that this process may be regulated by interactions with Th1 and Th17 cells (33). Our findings are also supported by lymphangiographic studies in a canine model of axillary lymphadenectomy demonstrating resolution of edema concurrent with development of hyperplastic collateral lymphatics that bypassed the zone of lymphatic injury (34). In the current study, in contrast to that by Ogata and colleagues, we found that macrophage depletion tended to accelerate development of progressive lymphedema, suggesting that the degree of lymphatic stasis is a major regulator of chronic inflammation and pathology.…”
Section: Discussionsupporting
confidence: 65%
“…Unlike our previous studies in large animals, the lymph nodes in rats were located more superficially, less than 1cm below the surface of the skin. 16,17 We could specify all the sentinel nodes once we cut the skin and used ICG lymphography to follow the course of each lymphatic vessel back to the node (Fig 2). The skin lymphatics connected to six groups of sentinel lymph nodes: superficial cervical, brachial, axillar, inguinal, gluteal and popliteal.…”
Section: Resultsmentioning
confidence: 99%
“…16-19 The brachial lymph node was located outside the axillary fossa, caudal from the triceps brachii and lateral from the lattismus dorsi. The lymphatic vessels in the forelimb and cranial part of the dorsal upper torso connected to this node.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite awareness regarding mammary lymphosomes, which are regional lymph drainage sites, several studies have shown that the presence of tumors may significantly alter the lymphatic direction as animals carrying mammary neoplasia undergo lymphatic reconfiguration due largely to the presence of prolymphangiogenic cytokines in the tumor's location [2]- [4].…”
Section: Introductionmentioning
confidence: 99%